Nucleotidyl transferase assisted DNA labeling with different click chemistries - Winz, Marie-Luise; Linder, Eva Christina; André, Timon; Becker, Juliane; Jäschke, Andres (Nucleic acids research, 2015)
Abstract. Here, we present a simple, modular and efficient strategy that allows the 3′-terminal labeling of DNA, regardless of whether it has been chemically o
Gesehen am 02.07.2020